Curriculum vitae: An important tool for the nurse practitioner. Issue 7 (2nd May 2016) - Hicks, Rodney W.; Roberts, Mary Ellen E.
Abstract: Advanced practice nurses (APNs) should maintain a curriculum vitae (CV) that comprehensively reflects the individual's work and professional accomplishments. This article guides APNs through best practices for development of a CV. Tips are offered to help guide the content, format, and maintenance of the CV.